Atomic Nanogenerators in Targeted Alpha Therapies: Curie’s Legacy in Modern Cancer Management - Mareike Roscher; Gábor Bakos; Martina Benešová (Pharmaceuticals, 2020)
Atomic in vivo nanogenerators such as actinium-225, thorium-227, and radium-223 are of increasing interest and importance in the treatment of patients with metastatic cancer diseases. This is due to their peculiar physical, chemical, and biological characteristics, leading to astonishing responses in otherwise resistant patients. Nevertheless, there are still a few obstacles and hurdles to be overcome that hamper the broader utilization in the clinical setting. Next to the limited supply and relatively high costs, the in vivo complex stability and the fate of the recoiling daughter radionuclides are substantial problems that need to be solved. In radiobiology, the mechanisms underlying treatment efficiency, possible resistance mechanisms, and late side effect occurrence are still far from being understood and need to be unraveled. In this review, the current knowledge on the scientific and clinical background of targeted alpha therapies is summarized. Furthermore, open issues and novel approaches with a focus on the future perspective are discussed. Once these are unraveled, targeted alpha therapies with atomic in vivo nanogenerators can be tailored to suit the needs of each patient when applying careful risk stratification and combination therapies. They have the potential to become one of the major treatment pillars in modern cancer management.